Similar prevalence of enteroviral genome within the myocardium from patients with idiopathic dilated cardiomyopathy and controls by the polymerase chain reaction. Issue 12 (December 1992) - Keeling, Philip J; Jeffery, Stephen; Caforio, Alida L P; Taylor, Rohan; Bottazzo, Gian F; Davies, Michael J; McKenna, William J
Abstract : Objective —To assess the prevalence and significance of enteroviral genome within myocardial biopsy specimens taken from patients with idiopathic dilated cardiomyopathy and from controls. Design —Prospective evaluation of myocardial tissue for the presence of an enteroviral genome by the polymerase chain reaction. Setting —A tertiary referral centre for patients with idiopathic dilated cardiomyopathy. Patients —Tissue for the study came from 50 consecutive patients with dilated cardiomyopathy, 41 with other forms of heart disease and 34 from coroners' necropsy cases. Results —Enteroviral genome was detected in 6/50 (12%) patients with dilated cardiomyopathy and 13/75 (17%) of the controls (not significant). No differences were seen between dilated cardiomyopathy patients with or without myocardial enteroviral genome in respect of age; duration of symptoms; proportion of patients with a premorbid acute viral illness, excess alcohol consumption, or hypertension; New York Heart Association functional class; measures of left ventricular function; or endomyocardial histology. Within the control group enteroviral genome was detected in 3/15 (20%) patients with ischaemic heart disease, 2/19 (10·5%) with valvar heart disease, 1/5 (20%) with specific heart muscle disease, 0/2 (0%) with congenital heart disease, and 7/34 (20·6%) cases of sudden death. During 2–52 month follow up (mean 22) 15/44 (34%) patients without myocardial enteroviral genome and 2/6 (33%) with myocardial enteroviral genome died suddenly or required orthotopic heart transplantation for progressive heart failure. Conclusions —These findings do not support the hypothesis that persistent enteroviral infection is of pathogenic or prognostic importance in dilated cardiomyopathy but they are consistent with enterovirus being a common environmental pathogen.